Popov Oleg Sergeyevich - article Editorial (Бюллетень сибирской медицины, 2003)
The creative biography of an authoritative surgeon of Tomsk, the head of general surgery clinic, a professor of the Siberian State Medical University O.S. Popov has been presented.